Adherence on Recommended Guidelines for Pre-Operative Routine Investigations in ASA (American Society of Anaesthesiologists) Grade 1 and 2 by Anaesthesiologists working at Tertiary Care Hospitals in the Province of Sindh - Hannan Ayub, Muhammad Zaid, Muhammad Saeed Siddiqui, Sana Javed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess adherence on recommended guidelines for pre-operative routine investigations in ASA grade 1 and 2 by anaesthesiologists. Study Design: Cross-sectional study Place and Duration of Study: Tertiary Care Hospitals in the Province of Sindh from 17th April 2019 to 17th October 2019. Methodology: One hundred anaesthesiologists were enrolled. The laboratory investigations of the patients which were ordered by anaesthesiologists according to ASA Grade I & II and surgical grade I & II depending upon the age (16-60). The investigations were classified into three categories Good, Acceptable and Poor depending upon adherence to NICE guidelines. Results: Sixty six (66%) were males and 34 (34%) were female and the median age was 31 (29-35). Only 16% were positive adherence to the NICE guidelines when ordering pre-operative routine investigations which falls under category of poor adherence while none of positive adherence fall under category of good or acceptable adherence. Traditionally, there is no recommended test for ASA I, surgery grades I & II and ASA II, surgery grade I, but the result indicates that several insignificant tests were requested in these classes. Conclusion: Preoperative biochemical testing is widely used and enhance the effectiveness of surgery but it should be cost effective in range of the patients. Keywords: Tertiary care hospitals, Adherence, Routine investigations, Guidelines